CompTIA A+ complete study guide - Docter, Quentin (Wiley publishing, 2007)
"Includes real-world scenarios, hands-on exercises, and leading-edge exam prep software featuring: custom testing engine, eight practice exams: 2 each for A+ essentials, IT technician, remote support technician, and depot technician, electric flashcards for PCs, pocket PCs, and Palm handhelds, entire book in PDF"-- Cover.